Analisis determinan infeksi menular seksual ibu rumah tangga - Silvia Ari Agustina; Liberty Barokah (Holistik Jurnal Kesehatan, 2021)
Determinant analysis of sexually transmitted infections in married womenBackground: Sexual health issues are increasingly becoming a worldwide concern, among others related to sexual behavior that affects the transmission of sexually transmitted infections (STIs). The rate of increase in Sexually Transmitted Infections sufferers in Indonesia is quite high compared to the scale of the population.Purpose: To analyze risk factors for sexually transmitted infections in married womenMethod: The subjects of this study were married women, with a total sample of 101, including a deep interview with 2 couples ( wives, and Husbands), Community Health Center staff serving sexually transmitted infections, and 1 Non-Governmental Organization. The sampling technique uses quota sampling. This type of research is a mixed-method with a sequential explanatory strategy and uses a cross-sectional study approach. Quantitative data collection techniques using closed questionnaires and for qualitative data with in-depth interviews. Analysis was used to determine risk factors for sexually transmitted infections using binomial logistic regression. The validity and reliability of qualitative data using triangulation of sources and methods.Results: There is a positive relationship between the incidence of STIs with the husband's work (OR: 10.07; 95% CI: 0.02-0.25; p: 0.000), family income (OR: 0.14; 95% CI: 0.04 -0.47; p: 0.001), condom use (OR: 3.25; 95% CI: 0.90-11.71; p: 0.001), and genital hygiene (OR: 8.25; 95% CI: 1,55-43,91; p: 0,013). Women as victims of unsafe husband's sexual behavior cause STI cases in married women to be high.Conclusion: Almost all IMS risk factors are positively related to IMS incidents, and husband employment has the greatest impact on IMS incidents in married women.Keywords: Sexually Transmitted Infections (STIs); behavior; risk factors; Married womenPendahuluan: Isu kesehatan seksual semakin menjadi perhatian dunia, antara lain terkait dengan perilaku seksual yang berdampak pada penularan penyakit Infeksi Menular Seksual (IMS). Angka peningkatan penderita Infeksi Menular Seksual di Indonesia cukup tinggi dibandingkan dengan skala penduduk.Tujuan: Menganalisis faktor risiko Infeksi Menular Seksual pada Ibu Rumah TanggaMetode: Subyek penelitian ini adalah Ibu Rumah Tangga, dengan total sampel 101, termasuk 2 Ibu Rumah Tangga, 2 Suami, petugas Puskesmas yang melayani penapisan Infeksi Menular Seksual dan 1 Lembaga Swadaya Masyarakat. Teknik sampling menggunakan quota sampling. Jenis penelitian ini mixed methodology dengan strategieksplanatoris sekuensialdan menggunakan pendekatan cross sectional study.Teknik pengambilan data kuantitatif dengan menggunaan kuesioner tertutup dan untuk data kualitatif dengan wawancara mendalam. Analisis yang digunakan untuk mengetahui faktor risiko IMS dengan menggunakan regresi logistik binomial. Validitas dan reliabilitas data kualitatif menggunakan triangulasi sumber dan metode.Hasil: Terdapat hubungan yang positif antara kejadian IMS dengan pekerjaan suami (OR:10,07; CI 95%:0,02-0,25; p:0,000), pendapatan keluarga (OR:0,14; CI 95%:0,04-0,47; p:0,001), penggunaan kondom (OR:3,25;  CI  95%:0,90-11,71;  p:0,001),  dan  higiene  genital  (OR:8,25;  CI  95%:1,55-43,91;  p:0,013).Perempuan sebagai korban dari perilaku seksual suami yang tidak aman menyebabkan kasus IMS pada ibu Rumah Tangga tinggi.Simpulan: Hampir semua faktor risiko IMS berhubungan positif dengan kejadian IMS, dan pekerjaan suami yang mempunyai pengaruh terbesar terhadap kejadian IMS pada Ibu Rumah Tangga